Elbert in the Air - Wesolowska, Monica, 1965-; Pumphrey, Jerome (New York : Dial Books for Young Readers, 2023)
Shortly after his birth, Elbert floats into the air and as he grows everyone tries to ground him, except for his mother, who encourages Elbert to be himself.
Keywords: Parent and child -- Juvenile fiction; Individuality -- Juvenile fiction; Growth -- Juvenile fiction; Juvenile fiction; African American boys -- Fiction; Individuality -- Fiction; Growth -- Fiction; Parent and child -- Fiction; Picture books